Figurative language intersubjectivity and usage - Soares da Silva, Augusto (Figurative thought and language,, 2021)
"Intersubjectivity and usage play central roles in figurative language and are pivotal notions for a cognitively realistic research on figures of thought, speech, and communication. This volume brings together thirteen studies that explore the relationship between figurativity, intersubjectivity and usage from the Cognitive Linguistics perspective. The studies explore the impact of figurativity on areas of lexicon and grammar, on real discourse, and across different semiotic systems. Some studies focus on the psychological processes of the comprehension of figurativity; other studies address the ways in which figures of thought and language are socially shared and the variation of figures through time and space. Moreover, some contributions are established on advanced corpus-based techniques and experimental methods. There are studies about metaphor, metonymy, irony and puns; about related processes, such as humor, empathy and ambiguation; and about the interaction between figures. Overall, this volume offers the advantages and the opportunities of an interactional and usage-based perspective of figurativity, embracing both the psychological and the intersubjective reality of figurative thought and language and empirically emphasizing the multidimensional character of figurativity, its central function in thought, and its impact on everyday communication"--